If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3x + -5) + -1(-1x + 4) = 0 Reorder the terms: (-5 + -3x) + -1(-1x + 4) = 0 Remove parenthesis around (-5 + -3x) -5 + -3x + -1(-1x + 4) = 0 Reorder the terms: -5 + -3x + -1(4 + -1x) = 0 -5 + -3x + (4 * -1 + -1x * -1) = 0 -5 + -3x + (-4 + 1x) = 0 Reorder the terms: -5 + -4 + -3x + 1x = 0 Combine like terms: -5 + -4 = -9 -9 + -3x + 1x = 0 Combine like terms: -3x + 1x = -2x -9 + -2x = 0 Solving -9 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 0 + 9 -2x = 0 + 9 Combine like terms: 0 + 9 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5
| 8-5/7x9 | | 6(3y-1)=14 | | 4x-6=-10(1) | | 720=(n-2)180 | | ln(x+5)+ln(x+5)=2ln(x+4) | | 17k^2-6k+3=3 | | -4y-0=3x-9 | | ln(x+4)-2=0 | | 1.2-w=1.2 | | y=2.3+1.8x | | x(3-2x)(5-2x)=0 | | 11-5x=28 | | 8f-f-5=44 | | 21-(16-5x)/2 | | senx=7 | | 5t/6-t/2 | | x=3x-38 | | 2x+7t=9 | | 21-16-5x/2 | | 8*4+7*(4+1)= | | f(x)=x+20 | | 2(y-8)-3(2y-5)= | | 1/2x-4=12/5-3/4x | | 8x+3=4x-8 | | 3x-38=23 | | 7k+9c-2k+3c= | | (5+x)+(x+4)=25 | | 12-10cosy=8 | | 7x-4y-30=0 | | 13/8-3/8 | | 6a+10-2a-2= | | b-8.1=11.9 |